Competition of Fairs on the Basis of the Composition Distribution - Prdić, Nedeljko (Industrija, 2017)
Optimization of competitiveness is one of basic elements of modern trade show marketing. The importance of competitiveness rapidly increases in last time. The goal of this work is finding recipes for optimization of competitiveness using analogies with natural nano processes. Here will be used analogy with Boltzmann’s distribution of particles on energy levels. The main difference consists in generalization of subjects of distribution. In Boltzmann’s theory, particles and energies are the basic subjects. Here we will be use terms "services” and "price of the service". The terms "services" and "price" have to be accepted in most general case. Due to the analogy with Boltzmann’s distribution, the distributions "services" – "price" are of exponential type with different parameters. Since the parameters of distributions can be different average values must be determined by means of resulting distribution, which is called composition. On the example of resulting distribution for two exponential distribution densities was concluded that average values, calculated over resulting distribution, are higher when parameters are close. This conclusion must be tested for the case of higher number of distributions.